Penguatan Karakter Religius untuk Meningkatkan Psychological Wellbeing pada Buruh Gendong Perempuan di Pasar Giwangan - Fitriah M Suud; Azam Syukur Rahmatullah; Mariah Kibtiyah (Universitas Mathla'ul Anwar Banten, 2021)
RELIGIOUS EDUCATION STRENGTHENING TO IMPROVE PSYCHOLOGICAL WELLBEING OF BURUH GENDONG WOMEN IN GIWANGAN MARKET. Everyone efforts to meet their needs are pursued in various ways in life. A unique thing that happens in Yogyakarta precisely in the Giwangan market is that a number of elderly women continue to make a living in surprising ways. Some elderly women, who were then called buruh gendong, lifted items that were more than normal. With a piece of striated batik cloth, they can lift weights of more than 50 kg. These buruh gendong work from morning till dawn. Its activities have been taken a long time until they have advanced age. Almost all of these workers are Muslims, the problem is that they are tired from working all day and the schedule cannot be ascertained, making them lose their time to worship and do not have time to study. Initial survey results show that many of them have not been able to read the Qur'an. So that this service aims to provide assistance in the context of strengthening the religious character, especially through the Qur'an recitation. The output of this service is expected to create a religious atmosphere in the Giwangan market. The workers work but also can maintain and feel the meaningfulness of their lives through mentoring to strengthen the religious character. This dedication works in collaboration with the Annisa Swasti Foundation (YASANTI), which has long accompanied them in the process of advocating and organizing workers in Yogyakarta.